Tafsir Konstitusional Batasan Moralitas, Rasionalitas dan Ketidakadilan Yang Intolerable dalam Pengujian Kebijakan Hukum Terbuka - Rayhan, Alendra Nauval Mufti; Safaat, Muchamad Ali; Murdiana, Elfa; Arssa, Ria Casmi (Universitas Islam Indonesia, 2026)
The discourse on legal policy has entered a new chapter in the judicial review of laws at the Constitutional Court. This new chapter is characterized by the Constitutional Court becoming increasingly open to reviewing open legal policies. Consequently, decisions previously deemed as open legal policies, such as cases concerning the presidential threshold, parliamentary threshold, and several other open legal policy cases, have begun to be granted by the Court. However, the ambiguity of meaning regarding morality, rationality, and intolerable injustice as limitations in the review of open legal policies creates obstacles for subsequent reviews. To that end, the researcher aims to seek the interpretation as well as the criteria of these limitations as the initial boundaries of open legal policy, formulated as: what is the meaning of the limitations of morality, rationality, and intolerable injustice in the review of open legal policy? This study employs a normative juridical research method with a conceptual approach that dissects the concept of limitations on open legal policy and a case approach utilizing Constitutional Court decisions that provide interpretations of the limitations of morality, rationality, and intolerable injustice. The purpose of employing these approaches is to ensure that the interpretation of the limitations of open legal policy holds constitutional value and reflects legal certainty within the concept of the rule of law. The researcher utilizes 16 (sixteen) decisions to discover this interpretation. Through these decisions, it is found that there are 6 (six) metrics of morality, 5 (five) metrics of rationality, and 4 (four) metrics of intolerable injustice commonly used by the Constitutional Court in reviewing open legal policies. These metrics are used to prove the constitutionality of open legal policies in the judicial review of laws